Soil microbial communities associated with two commercially important plant species indigenous to the fynbos region of South Africa : cyclopia spp. (honeybush) and Aspalathus linearis (rooibos) - Postma, Anneke (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.